Assessment of the interactions between cetaceans and fisheries at the south of the Cetacean Migration Corridor and neighboring waters (Western Mediterranean) - Izquierdo-Serrano, Mar; Revuelta, Ohiana; Míguez-Lozano, Raúl; Gozalbes, Patricia; Ruiz-García, David; Raga, Juan Antonio; Tomás, Jesús (Frontiers in Marine Science, 2022)
The Cetacean Migration Corridor is an important marine protected area for cetacean species in the Western Mediterranean, and part of its waters constitute the main fishing grounds for the Valencia region (East Spain) fishing fleet. Here we aim to assess the interactions between all active fisheries operating in the waters of the Valencia region and the cetacean species inhabiting this area. A total of 282 face-to-face interviews (51.37% of the total fleet) to fishers were held on 20 ports at the study area to gather information about cetacean by-catch and all types of interactions between fisheries and cetaceans. The interviewed bottom trawlers (n = 148 boats) reported a monthly by-catch rate (C) of 0.01 dolphins per vessel. Bottom trawling vessels operating at neritic zones only reported by-catch of common bottlenose dolphin (C = 0.009), while those fishing at oceanic zones by-caught striped dolphin (C = 0.006) and common bottlenose dolphin (C = 0.003). The interviewed artisanal fishers (n = 114 boats), the second most important fishery in the study area, only reported one dolphin by-catch event, but 90 of these boats communicated continued negative interactions with the common bottlenose dolphin, causing gear damage and catch take. The interviewed vessels gave an estimation of their annual economic loss produced by this interaction (mean ± SD: 2,998.10 ± 2095.02 € per boat). Other fisheries operating in the Valencia region were purse-seiners (n = 15 boats) and pelagic longlines, a fishery that has almost disappeared in the study area (n = 5 boats). The first one had the highest estimated dolphin by-catch rate (C= 0.04) and mainly interacted with common bottlenose dolphin, but also with striped dolphin. The information gathered from interviews was complimented with long-term stranding data (1990–2020). Despite the fact that only 7.80% of all recorded stranded cetaceans showed fisheries interaction signs, 26.72% of the common bottlenose dolphins recorded showed evidence of this interaction, thus confirming that it is the cetacean species most affected by fisheries in the area. Records of stranded striped dolphin (6.45%) also showed evidence of fisheries interaction. Based on both dolphin by-catch and gear damage, management plans are needed in the area to ensure cetacean conservation and also fisheries sustainability in waters inside and around marine protected areas at the Spain’s Mediterranean.